Borders as peace project - McCall, Cat (Politica, 2020)
Peacebuilding in European borderscapes stresses contact, communication and cooperation across borders and across ethnic and national boundaries. Respect for cultural difference is the guiding principle of this enterprise with the aim of tackling fear and mistrust, addressing grievances, and challenging stereotypes. Nevertheless, it is not multicultural respect but economic cooperation that has been the main priority of European Union cross-border cooperation initiatives. Addressing the legacy of border conflict and the residual emotions of suspicion, fear, resentment, grievance and hatred has been, at best, a secondary concern. This is complicated further by the twenty-first century fixation on the securitisation of borders, with cross-border cooperation aimed at securing the European Union’s external frontier. In this twenty-first century context of rebordering, the path of European integration could well shift from one of intergovernmental and cross-border peacebuilding to one that appeals to Europe’s legacy of border conflict and coercion.